Optimalisasi Kinerja UMKM melalui Pendampingan Inovasi dan Keuangan Digital - Dewi, Luh Komang Candra; Yogantara, Komang Krishna; Sujadi, Dewiwati (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service program aims to optimize MSMEs performance through product innovation assistance and financial digitalization in Bedulu Village, Blahbatuh District, Gianyar Regency. The main problems faced by MSMEs include limited product innovation, inadequate human resource management, and non-systematic financial recording practices. The program applied a participatory approach consisting of problem identification, training sessions, hands-on mentoring, and evaluation. The activities were conducted by a team of lecturers and KKN students, covering product innovation, human resource development, and basic digital financial literacy practices. The results indicate an improvement in participants’ understanding and skills in developing product variations and packaging innovation, as well as implementing simple digital financial recording. MSMEs actors also demonstrated better awareness of separating personal and business finances. Overall, the program positively contributed to strengthening managerial capacity and enhancing MSMEs’ readiness to compete in the digital market environment. Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mengoptimalkan kinerja UMKM melalui pendampingan inovasi produk dan digitalisasi keuangan di Desa Bedulu, Kecamatan Blahbatuh, Kabupaten Gianyar. Permasalahan utama yang dihadapi mitra meliputi rendahnya inovasi produk, keterbatasan pengelolaan sumber daya manusia, serta belum optimalnya pencatatan keuangan berbasis digital. Metode pelaksanaan menggunakan pendekatan partisipatif melalui tahapan identifikasi masalah, pelatihan, pendampingan praktik, serta evaluasi. Kegiatan dilaksanakan oleh tim dosen dan mahasiswa KKN dengan memberikan materi inovasi produk, pengembangan SDM, serta literasi dan aplikasi keuangan digital sederhana. Hasil kegiatan menunjukkan adanya peningkatan pemahaman dan keterampilan pelaku UMKM dalam melakukan inovasi kemasan dan variasi produk, serta kemampuan menyusun pencatatan keuangan digital secara lebih sistematis. Selain itu, pelaku usaha mulai memahami pentingnya pemisahan keuangan pribadi dan usaha. Program ini memberikan dampak positif terhadap peningkatan kapasitas manajerial dan kesiapan UMKM dalam menghadapi persaingan pasar berbasis digital.